Ingestion and polymeric risk assessment of microplastic contamination in commercially important brachyuran crab Portunus sanguinolentus - Rabari, Vasantkumar; Patel, Heris; Ali, Daoud; Yadav, Virendra Kumar; Patel, Ashish; Sahoo, Dipak Kumar; Trivedi, Jigneshkumar (Frontiers in Marine Science, 2023)
Microplastic (MP) in seafood is a growing area of food safety. In the present study, MP contamination in the commercially important crab Portunus sanguinolentus was assessed. A total of 300 crab specimens were collected from three principal fishing harbors of Gujarat. The collected specimens were analyzed for MPs isolation using a previously published protocol. The specimens were dissected, and organs such as the gut and gills were placed separately in the beaker. The organic tissues were digested using 10% KOH. After the digestion, flotation and filtration processes were carried out for the extraction of MPs. The physical (shape, size, and color) and chemical characterization of MPs were performed. The average abundance of MP was recorded as 0.67 ± 0.62 MPs/g. The pollution indices revealed very high contamination and fell under class IV (Jakhau) and V risk categories (Okha and Veraval). Microfibers were found dominantly. Blue and black-colored MPs with 1–2 mm sizes were recorded dominantly. Polyethylene, polyethylene tetraphene, polyurethane, polystyrene, and polypropylene were identified as polymer compositions of MPs. Concludingly, the present study gives an insight into the MP in an important crab species P. sanguinolentus, which can be useful to design further investigations on the toxicity of MPs in seafood.